Repeat Colonoscopy within 6 Months after Initial Outpatient Colonoscopy in Ontario: A Population-Based Cross-Sectional Study - Lawrence Paszat; Rinku Sutradhar; Nancy N. Baxter; Jill Tinmouth; Linda Rabeneck (Canadian Journal of Gastroenterology and Hepatology)
Background. The goal of this study is to examine utilization of early repeat colonoscopy ≤ 6 months after an index procedure. Methods. We identified persons having repeat colonoscopy ≤ 6 months following outpatient colonoscopy without prior colonoscopy ≤ 5 years or prior diagnosis of colorectal cancer (CRC). We modeled repeat colonoscopy using a generalized estimating equation with an exchangeable correlation structure to account for clustering of patients by endoscopist. Results. The population included 334,663 persons, 7,892 (2.36%) of whom had an early repeat colonoscopy within 6 months. Overall, endoscopist prior year colonoscopy volume was inversely related to repeat ≤ 6 months. Repeat colonoscopy ≤ 6 months varied by the clinical setting of the index colonoscopy (adjusted OR = 1.41 (95% CI 1.29–1.55)) at nonhospital facilities compared to teaching or community hospitals. Among those who had polypectomy or biopsy, the adjusted OR for early repeat ≤ 6 months was elevated among those whose index colonoscopy was at a nonhospital facility (OR 1.44, 95% CI 1.30–1.60), compared to those at a teaching hospital or community hospital. Conclusions. Repeat colonoscopy ≤ 6 months after an index procedure is associated with the clinical setting of the index colonoscopy.